Molecular Mechanisms Underlying the Therapeutic Role of Vitamin E in Age-Related Macular Degeneration - Edwards, Genea; Olson, Caroline G.; Euritt, Carlyn P.; Koulen, Peter (Frontiers in Neuroscience, 2022)
The eye is particularly susceptible to oxidative stress and disruption of the delicate balance between oxygen-derived free radicals and antioxidants leading to many degenerative diseases. Attention has been called to all isoforms of vitamin E, with α-tocopherol being the most common form. Though similar in structure, each is diverse in antioxidant activity. Preclinical reports highlight vitamin E’s influence on cell physiology and survival through several signaling pathways by activating kinases and transcription factors relevant for uptake, transport, metabolism, and cellular action to promote neuroprotective effects. In the clinical setting, population-based studies on vitamin E supplementation have been inconsistent at times and follow-up studies are needed. Nonetheless, vitamin E’s health benefits outweigh the controversies. The goal of this review is to recognize the importance of vitamin E’s role in guarding against gradual central vision loss observed in age-related macular degeneration (AMD). The therapeutic role and molecular mechanisms of vitamin E’s function in the retina, clinical implications, and possible toxicity are collectively described in the present review.